1997
DOI: 10.1093/oxfordjournals.aje.a009191
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Environments and Coronary Heart Disease: A Multilevel Analysis

Abstract: The authors investigated whether neighborhood socioeconomic characteristics are associated with coronary heart disease prevalence and risk factors, whether these associations persist after adjustment for individual-level social class indicators, and whether the effects of individual-level indicators vary across neighborhoods. The study sample consisted of 12,601 persons in four US communities (Washington County, Maryland; Forsyth County, North Carolina; Minneapolis, Minnesota; and Jackson, Mississippi) partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
414
2
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 638 publications
(444 citation statements)
references
References 60 publications
18
414
2
4
Order By: Relevance
“…Neighborhood SES has been shown to play an important role in health. Several studies have found that persons living in poorer residential neighborhoods have an increased prevalence of cardiovascular risk factors 5 and higher incidence of hypertension, 10 diabetes, 22 obesity, 6 and CVD. 4,45 Diez-Roux and colleagues observed that residence in lower SES neighborhoods was associated with increased odds of smoking, elevated systolic blood pressure, and serum cholesterol levels after adjustment for individual-level variables in the Atherosclerosis Risk in Communities (ARIC) study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neighborhood SES has been shown to play an important role in health. Several studies have found that persons living in poorer residential neighborhoods have an increased prevalence of cardiovascular risk factors 5 and higher incidence of hypertension, 10 diabetes, 22 obesity, 6 and CVD. 4,45 Diez-Roux and colleagues observed that residence in lower SES neighborhoods was associated with increased odds of smoking, elevated systolic blood pressure, and serum cholesterol levels after adjustment for individual-level variables in the Atherosclerosis Risk in Communities (ARIC) study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Neighborhood socioeconomic status (SES) has been found to be inversely associated with CVD risk. 4,5 In addition, compared to residents of wealthier neighborhoods, residents of disadvantaged neighborhoods are more likely to be overweight or obese, [6][7][8] to smoke, 5,9 and to have higher blood pressure, 5,8,10 lipid levels, 4,8 and glucose levels. 8,11 Inflammation plays a critical role in all stages of the CVD disease process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies (8,30,31) applied hierarchical linear modelling or logistic regression. In the current study, we take a latent class (LC) approach and simultaneously identify consumer segments at both the individual level and the food retail environmental level.…”
Section: Discussionmentioning
confidence: 99%
“…Fast food is high in energy and low in micronutrient density, and fast-food consumption may contribute to the obesity epidemic (4)(5)(6) . Although research on the possible interactions between obesity and characteristics of the food environment is at an early stage and the evidence is currently too weak to draw firm conclusions (7) , US studies suggest that the food environment influences a healthy diet and obesity levels in North America (8)(9)(10) .The clearly observable presence of processed foods, fast-food restaurants, supermarkets and other food outlets as factors determining the rising prevalence of overweight and obesity is a topic of research that is particularly relevant in the context of developed countries. Similar to the changing food retailing landscape in the postWorld War II era in Western countries (11,12) , the food retailing sector in China is experiencing dramatic changes half a century later.…”
mentioning
confidence: 99%